Effectiveness of different selection indices for genetic improvement in Murrah buffaloes - KURALKAR, S V; RAHEJA, K L (The Indian Journal of Animal Sciences, 2013)
Eleven selection indices incorporating first lactation traits, viz. age at first calving, first lactation milk yield, first lactationlength and tirst calving interval of buffaloes, were constructed and compared. Results indicated that selection based on anindex containing first lactation milk yield and first lactating length was best which will bring maximum simultaneous geneticgain in these traits and as well as in total aggregate genetic merit.